Physician's guide to arthropods of medical importance - Goddard, Jerome (Taylor & Francis, 2013)
The sixth edition continues the previous tradition, in that the information provided is practical and presented in a format optimal for use on an as-needed basis. The addition of color photographs throughout the text (and not just an insert) is a major plus. Additional clinical case histories enliven the text. General guidelines to treatment of conditions resulting from exposure to arthropods and appropriate references to detailed material are also provided. Another aspect, the 'Bug Coach' CD-ROM, provides over 100 line drawings, figures, and photos in three sections: (1) arthropods, (2) arthropod-induced diseases and conditions, and (3) an identification guide. The CD also now includes a few brief instructional videos